The Combined Quantification and Interpretation of Multiple Quantitative Magnetic Resonance Imaging Metrics Enlightens Longitudinal Changes Compatible with Brain Repair in Relapsing-Remitting Multiple Sclerosis Patients - Bonnier, Guillaume; Maréchal, Benedicte; Fartaria, Mário João; Falkowskiy, Pavel; Marques, José P.; Simioni, Samanta; Schluep, Myriam; Du Pasquier, Renaud; Thiran, Jean-Philippe; Krueger, Gunnar; Granziera, Cristina (Frontiers in Neurology, 2017)
Objective: Quantitative and semi-quantitative MRI (qMRI) metrics provide complementary specificity and differential sensitivity to pathological brain changes compatible with brain inflammation, degeneration and repair. Moreover, advanced MRI metrics with overlapping elements amplify the true tissue-related information and limit measurement noise. In this work, we combined multiple advanced MRI parameters to assess focal and diffuse brain changes over 2 years in a group of early-stage relapsing-remitting MS patients. Methods: Thirty relapsing-remitting MS patients with less than 5-year disease duration and nine healthy subjects underwent 3T MRI at baseline and after 2 years including T1, T2, T2* relaxometry, and magnetization transfer imaging. To assess longitudinal changes in normal-appearing tissue and lesions, we used analyses of variance and Bonferroni correction for multiple comparisons. Multivariate linear regression was used to assess the correlation between clinical outcome and multiparametric MRI changes in lesions and normal appearing tissue. Results: In patients, we measured a significant longitudinal decrease of mean T2 relaxation times in normal appearing white matter (p = 0.005) and a decrease of T1 relaxation times in the pallidum (p < 0.05), which are compatible with edema reabsorption and/or iron deposition. No longitudinal changes in qMRI metrics were observed in controls. In MS lesions, we measured a decrease in T1 relaxation time (p-value < 2.2e-16) and a significant increase in MTR (p-value < 1e-6), suggesting repair mechanisms such as remyelination, increased axonal density and/or a gliosis. Last, the evolution of advanced MRI metrics - and not changes in lesions or brain volume - were correlated to motor and cognitive tests scores evolution (Adj-R2 > 0.4, p < 0.05). In summary, the combination of multiple advanced MRI provided evidence of changes compatible with focal and diffuse brain repair at early MS stages as suggested by histopathological studies.